2004
DOI: 10.1038/sj.jp.7211034
|View full text |Cite
|
Sign up to set email alerts
|

An Amniotic Fluid Index ≤5 cm Within 7 Days of Delivery in the Third Trimester Is Not Associated with Decreasing Umbilical Arterial pH and Base Excess

Abstract: OBJECTIVE:To determine if an amniotic fluid index (AFI) r5.0 cm within 7 days of delivery in the third trimester is associated with decreasing umbilical arterial pH and base excess. STUDY DESIGN:Cases for this retrospective cohort study were all pregnancies Z26 weeks with intact membranes and an AFI r5.0 cm within 7 days of delivery between 11/99 and 7/02. Multiple gestations, aneuploid, and anomalous fetuses were excluded. Controls with an AFI >5.0 cm within 7 days of delivery were matched to each case within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
2
12
1
1
Order By: Relevance
“…In the study by Tajinder et al the mean AFI in the study group (AFI=5) was 3.605 ± 1.1490 cm and in control group (AFI >5) was 12.001 ± 3.520 cm. In Driggers et al [9] the mean AFI in cases was 3.0 ± 1.5 cm and in controls was 10.7 ± 4.0 cm; which were similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Tajinder et al the mean AFI in the study group (AFI=5) was 3.605 ± 1.1490 cm and in control group (AFI >5) was 12.001 ± 3.520 cm. In Driggers et al [9] the mean AFI in cases was 3.0 ± 1.5 cm and in controls was 10.7 ± 4.0 cm; which were similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…The 5-min Apgar score was statistically insignificant between the groups (1 vs. 7 %). In similarity to this study, Driggers et al [12] observed that a 5-min Apgar score <7 in 3.8 % patients in an oligohydramnios group versus 4.6 % in a normal AFI group were not significant to each other. A study by Grubb et al [13] reported that the 1-min Apgar score <7 in 84 % patients with AFI ≤ 5 as compared to 14 % in the normal AFI group, which was statistically highly significant (p = 0.4140.…”
Section: Resultssupporting
confidence: 50%
“…A study by Driggers et al 13 reported at 5 min APGAR score of <7 in 3.8 % patients in an oligohydramnios group vs 4.6 % in a normal AFI group and concluded that there was no significnant difference. A study by Grubb et al 14 was found that 1 min APGAR score of <7 in 84% of patients with AFI of <5 as compared to 14 % in normal AFI groups which was highly significant (p=0.01). In the same study, 5 min score of <7 was seen in 13% patients with AFI of ≤ 5 cm vs 5% in normal AFI group.…”
Section: Discussionmentioning
confidence: 86%